엘리트 여자 축구선수의 철분보충이 체내 철분상태와 면역 및 항산화에 미치는 영향 - 강형숙(Kang Hyung Sook); 김혜영(Kim Hye-Young); 조여원(Choue Ryowon) (Hanʼguk yongyang hakhoe chi, 2003)
This study was performed to evaluate the effect of iron supplement for 4 weeks on iron status, immunity, and antioxidant status of national female soccer players (n = 25). This study was performed at summer hard training period right before competition. A single blind design was used to divide the subjects into iron-supplement (IS) or placebo group (P). Iron-supplement group was supplemented with iron (40 mg/d) for 4 weeks. The mean age of the subjects was 23.3 $±$ 2.5 years old. Mean height and body weight of the subjects were 164.4 $±$ 5.7 em and 57.4 $±$ 4.6 kg, respectively. The mean carrier as soccer player was 11.0 $±$ 2.6 years and mean training time was 7.0 $±$ 1.3 hr/day. The mean hemoglobin, hematocrit, total iron binding capacity and ferritin concentrations before iron supplementation were not different between two groups. After 4 weeks of summer training and iron supplementation, serum ferritin level was significantly increased only in IS group after supplementation. Mean corpuscular volume and total iron binding capacity were significantly decreased in both groups. Meanwhile, hemoglobin and red blood cell count were significantly lowered only in placebo group. The IgM concentration increased significantly in both groups, but IgG concentration had increasing tendency only in IS group (p < 0.064). Therefore, iron supplementation during hard training period may be helpful to improve work capacity of the athletes by improving ferritin status and humoral immune responses.